OECD Infrastructure Governance Indicators Conceptual framework, design, methodology and preliminary results - Ruiz Rivadeneira, Ana Maria (OECD Working Papers on Public Governance, 2023)
The governance of infrastructure can affect how and whether infrastructure projects achieve desired outcomes and contribute to wider policy goals. This paper presents the conceptual framework, design and methodology of the OECD Infrastructure Governance Indicators (IGIs). The IGIs support the implementation and monitoring of the OECD Recommendation on the Governance of Infrastructure. This paper also describes the key findings from the first set of IGIs, which cover three areas: long-term strategic vision for infrastructure; fiscal sustainability, affordability and value for money; and efficient and effective public procurement. It identifies the governance dimensions that are well developed across OECD countries and those that require improvements under each of the three areas